Accelerated T2 Mapping of the Lumbar Intervertebral Disc: Highly Undersampled K-Space Data for Robust T2 Relaxation Time Measurement in Clinically Feasible Acquisition Times. Issue 11 (November 2020) - Raudner, Marcus; Schreiner, Markus; Hilbert, Tom; Kober, Tobias; Weber, Michael; Windhager, Reinhard; Trattnig, Siegfried; Juras, Vladimir
Objectives: T2 mapping of the intervertebral disc (IVD) can depict quantitative changes reflecting biochemical change due to loss of glycosaminoglycan content. Conventional T2 mapping is usually performed using a 2-dimensional multi-echo-spin echo sequence (2D-MESE) with long acquisition times that are generally not compatible with clinical routine. This study investigates the applicability of GRAPPATINI, a T2 mapping sequence combining undersampling, model-based reconstruction, and parallel imaging, to offer clinically feasible acquisition times in T2 mapping of the lumbar IVD. Materials and Methods: Fifty-eight individuals (26 female; mean age, 23.3 ± 8.1 years) were prospectively studied at 3 T. GRAPPATINI was conducted with the same parameters as the 2D-MESE while shortening the acquisition time from 13:18 to 2:27 minutes. The setup was also validated in a phantom experiment using a 6.48-hour-long single echo-spin echo sequence as reference. The IVDs were manually segmented on 4 central slices. Results: The median nucleus pulposus showed a strong Pearson correlation coefficient between T2GRAPPATINI and T2MESE ( r p = 0.919; P < 0.001). There was also a significant correlation for the ventral ( r p = 0.241; P < 0.001) and posterior ( r p = 0.418; P < 0.001) annular regions. In the single spin-echo phantom experiment, the most accurate T2 estimation was achieved using T2GRAPPATINI with a median absolute deviation of 15.3 milliseconds as compared with T2MESE with 26.5 milliseconds. Conclusions: GRAPPATINI facilitates precise T2 mapping at 3 T in accordance with clinical standards and reference methods using the same parameters while shortening acquisition times from 13:18 to 2:27 minutes with the same parameters.